A first-principles study on the hydrogen trap characteristics of coherent nano-precipitates in α-Fe. (16th October 2020) - Ma, Yuan; Shi, Yufang; Wang, Heyuan; Mi, Zhishan; Liu, Zugang; Gao, Lei; Yan, Yu; Su, Yanjing; Qiao, Lijie
Abstract: Density functional theory (DFT) calculations have been carried out to investigate the hydrogen trap characteristics of a serial of nano-precipitates (VC, VN, TiN, NbN, NbC, and NiAl) in α-Fe. The H atom solution energies calculations in bulk nano-precipitates indicate that ideal nano-precipitates could not trap H atoms, while the vacancies in nano-precipitates could reduce the H atom solution energies. With respect to the coherent interfaces between α-Fe and nano-precipitates, tetrahedral sites are possible hydrogen traps. Volume evolutions and Bader charge analyses have been performed and it was found the strain at the coherent interface benefits to the hydrogen trap. In addition, the vacancies near the coherent interfaces could be fine hydrogen traps, which is attributed to the combined effect of strain and vacancy. This study could provide guidance to design nano-precipitates in steel to suppress the hydrogen embrittlement. Highlights: Hydrogen trap characteristics of nano-precipitates in α-Fe are studied by DFT. Ideal nano-precipitates could not trap H atoms. Strain at the coherent interface of α-Fe/nano-precipitate benefits to hydrogen trap. Vacancies near coherent interface of α-Fe/nano-precipitate are fine hydrogen traps.